APLIKASI UNSUR BUDAYA BETAWI SEBAGAI HIASAN RUANGAN - Thufail; Nitiyoga, Rio Yohanes; Cikal Haekal, Muhammad (AMARASI: JURNAL DESAIN KOMUNIKASI VISUAL, 2024)
The shape of the Betawi traditional house as a cultural heritage is very inspiring for packaging designers to make it into a Public Relations (PR) Package. Along with the times, people in the Jakarta area are increasingly starting to abandon the traditional Betawi house form and prefer to build houses with a more modern and minimalist theme or start living in apartments. For this reason, packaging designers were inspired to create a PR Package by taking the shape and structure of the Betawi traditional house, and then from a visual perspective. PR Package is always used for promotional and marketing purposes, therefore the main focus of this research is to explore what characteristics exist in Betawi traditional houses which later the results of the identification will be used as inspiration in making PR Package designs. The method of data collection is done by exploration and direct observation of the elements that exist in Betawi culture. After the findings are obtained, this research is expected to contribute to further developments in the domain of PR Package design and interior design, as well as provide new insights into the importance of making creative and inspiring PR Package designs as one of the media in preserving culture in Indonesia and at the same time as a way to promote local culture and products to foreign countries.